Gender Based Students’ Learning Autonomy in English Flipped Classroom - Leni Irianti; Syafryadin Syafryadin; Elda Resi Moneta Wibowo; R.Bunga Febriani (Linguists : Journal Of Linguistics and Language Teaching, 2021)
This research is aimed at finding out the effectiveness on applying flipped classroom to enhance learning autonomy and how its impact on gender based students’ learning autonomy. The researchers was applied convergent parallel mixed methods design. The populations of this study were senior high school in Pangandaran and the researchers selected a particular class. The class which participated is X MIPA 4 which consist of 11 male and 19 female as the experimental group and X MIPA 1 as the control one which consist of 12 male and 18 female. The totals of participants are 60 students. The data collected from pre-post Learning Autonomy Questionnaire (LAQ) and pretest-posttest as quantitative data and interview as qualitative data. The questionnaire was analyzed by using SPSS 16.0 for Windows. The result showed there is a significant difference in students’ learning autonomy between students who are taught by means of flipped classroom and those who are not. Moreover, female indicates more autonomy than male in both class even before or after the treatment. Pretest-posttest indicated although the score of autonomy is increased, it does not have significant impact on their narrative reading comprehension test. On the other hand, based on the interview both female and male students respond positively about applying flipped classroom to enhace their learning autonomy even though there is no huge difference for male. In conclusion, flipped classroom has given a good impact in students’ learning autonomy even for female or male students although not give significant impact in students’ learning outcomes especially in narrative reading comprehension.